Educational Innovation with Agile Methodologies: Scrum and Design Thinking for Competence Development in Academic Projects in Peru - Riojas Rivera, Jimmy Ronald; Mejia De Paz, Octavio David; PANTA CHUNGA, MARY INOCENCIA; Duran Herrera, Víctor Hugo; NIEVES BARRETO, CONSTANTINO MIGUEL; DURAND GONZALES, CESAR ANGEL; ALEJOS IPANAQUÉ, RUFINO (LACCEI, 2025)
This study explores the implementation of agile methodologies in higher education in Peru, focusing on the application of EduScrum and Design Thinking in academic projects. A teaching experience was conducted through two sprints, where students assumed different roles within the Scrum framework. The results indicate a strong preference for teamwork and a tendency to take on the Scrum Master role, suggesting high leadership potential. Additionally, a moderate to strong positive correlation (ρ = 0.626, p < 0.01) was found between Design Thinking and Elevator Pitch skills, highlighting the importance of both methodologies in fostering communication and innovation competencies.